Influencer Marketing and Consumer Purchase Intentions in the Fast Fashion Industry - Jing Foo Yee; Padmalini Singh; Lay Hong Tan; Jin Cong Yap; Xin Yuan Xiong; Zi Yang Xie; Quan Cheng Yao; Deepika V; Daisy Mui Hung Kee (Journal of The Community Development in Asia, 2026)
The rapid growth of social media has intensified the use of influencer marketing in the fast fashion industry, reshaping how consumers form purchase intentions. Despite its widespread application, empirical evidence on influencer effectiveness in the Malaysian fast fashion context remains limited. This study aims to examine the influence of key influencer attributes: trustworthiness, credibility, expertise, and familiarity, on consumer purchase intention, using Padini Holdings Berhad as a case study. A quantitative research design was employed, with data collected from 150 respondents through a structured questionnaire. Multiple regression analysis was conducted to test the proposed relationships. The results indicate that the research model explains 74.8% of the variance in purchase intention (R² = 0.748). Familiarity of the influencer emerged as the strongest predictor (? = 0.414, p 0.01), followed by expertise (? = 0.258, p 0.01) and credibility (? = 0.218, p 0.05). In contrast, trustworthiness showed a positive but statistically insignificant effect. These findings suggest that emotional connection, perceived knowledge, and credibility play a more critical role than trustworthiness in driving purchase intention within the fast fashion sector. Practically, the study highlights the importance of selecting influencers who are familiar, knowledgeable, and relatable to enhance marketing effectiveness.